PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PERENCANAAN KARIR SISWA DALAM MEMASUKI PERGURUAN TINGGI KELAS X SMA NEGERI 2 PEKANBARU TAHUN PELAJARAN 2014/2015 - Witriani, Rahmawati; ', Rosmawati; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The students’ career planning can be increased by the guidance services group. This study aims to reveal the students career planning before implementation guidance services group. To know the process of implementation of guidance services group to the student career planning. To describe the students career planning implemented after guidance services group. To determine differences in students career planning implemented before the after guidance services group. To find out how much influence the guidance services group to students career planning. In this study, using a pre-experimental design with one group pretest-posttest design. The subjects were students of class X MIA 3 and class X IIS 2 SMA Negeri 2 Pekanbaru academic year 2014/2015 totaling 30 students. To distinguish the career planning of students before and after using the test guidance services group 't' and obtained prices t_count greater than the price of t_tables at 5% level (10.93> 2,000). Thus, Ho is rejected and Ha accepted which means this study there are significant differences between students career planning before and after the service conducted group guidance class X SMA Negeri 2 Pekanbaru. Then the results of the test product moment r = 0.54 and coefficient determinant = 0.29. Based on the results of research conducted it can be concluded that once implemented guidance services group on career planning for college students in class X SMA Negeri 2 Pekanbaru increased by 29%.Keywords: Guidance Services Group, Career Planning